Structured product pricing using Monte Carlo simulations - Teo, Kang Sheng (Nanyang Technological University, 2021)
The purpose of this paper is to fairly price a structured product by using Monte Carlo simulations under the risk neutral measure, and also to learn how to control the risk of the product. A structured product that is commonly offered, the Barrier Reverse Convertible, is chosen and priced in this paper. We first explore two different models for the underlying assets of the product, namely the Black-Scholes model and the GARCH model. The two models are fitted to the underlying assets and simulations are done to give an estimate of the fair price of the product. The Value at Risk(VaR) is then calculated to measure and quantity the level of financial risk of the product under the two different models. The empirical results show that the product has been slightly overpriced as compared to the price of the product set by the issuer. Although the price difference is small, great care and more research has to be taken before deciding to invest in the product. This study can be extended by considering other types of structured products or other models that can be used to model the stock prices and their returns.